Parables for Now - Kallarakal, Abraham (Journal of Dharma, 1982)
Books on Biblical themes especially on the New Testament is of much use and demand of the age. Now, Edmund Flood, with his paramount experience in this field brings to light the dynamism of the New Testa- ment parables. It has four chapters. In the first chapter, the author analyses "the Jesus' method" of preaching the good news. The second chapter contains five parables which highlight the real nature and work of the person of Jesus. The six parables reflected upon in the third chapter speak about some of the implications of following Jesus.